دراسة تجريبية وتحليلية لرفع كفاءة البلاطات البيتونية المسلحة المستخدمة في الظروف المحلية - كيخيا عبد الحميد (Latakia University Journal -Engineering Sciences Series, 2016)
Slabs are considered one of the most exposed elements to disasters and deformities that can be clear to the viewer. These deformities are reflected as sign of defects that appear clearly on big slabs. So, here comes the importance of applying and designing accurate slabs. The purpose of this research is stating the need for persistent efforts to get a better form of the slabs in order to increase their ability to be able to carry any outside extra weights without the appearance of any deformities that might take place during the period of investing the building. When deformities happen, they have bad effect on the beauty and main function (purpose) of the building. This research includes an experimental study for the real applicable slabs under our supervision, in addition to a theoretical study about the deflection appearing on the slabs by taking into consideration the plastic specifications of the concrete and the formation of cracks. This research aims at constructing reflexive deflections in the slabs during the construction period and measuring the actual deformities and watching them through a period of time, then comparing them with the theoretical expected deformities. The findings that we could get at the end of our research are supposed to play a main role in choosing the best design for the mandate slabs and at the same time getting the best value for the reflexive deflection that can be used in the slab to make it better functionally and to increase its ability to resist the outside applied weights. We hope this is just a start for more research in this field. تعتبر البلاطات من أهم العناصر في الجملة الإنشائية ، إذ إنها تشكل بحدود 60% من حجم البيتون المسلح الإجمالي للبناء [1]. من هنا فإن اختيار التصميم المناسب للبلاطات يعتبر من المسائل الأساسية التي يجب أخذها بعين الاعتبار عند تصميم الأبنية . من جهة أخرى فإن حمولات الزلازل تتعلق بشكل رئيسي بالوزن الذاتي للبناء ، وبالتالي فإن حجم البلاطات يلعب الدور الرئيس في تصميم العناصر الإنشائية الأخرى ( الجوائز ، الأعمدة ،جدران القص ، القواعد ) للبناء. هدف هذا البحث هو السعي للوصول إلى تصميم أفضل ( اختيار الأبعاد المناسبة ) للبلاطات البيتونية المسلحة لرفع كفاءتها لتقاوم الحمولات الخارجية المطبقة ، وتحقيق أكبر ريعية اقتصادية في استخدام المواد ، وتلافي أي احتمال لظهور تشوهات قد تحدث خلال عملية استثمار المبنى ،تؤثر سلباً في الناحية الوظيفية والجمالية للمبنى . يتضمن البحث إجراء دراسة تجريبية على بلاطات حقيقية ، ودراسة نظرية على السهوم المتشكلة في البلاطات مع الأخذ بعين الاعتبار الخواص اللدنة للبيتون. فكرة البحث هي تنفيذ سهوم معاكسة في البلاطات في مرحلة الإنشاء، وقياس التشوهات الفعلية المتشكلة ومراقبتها مع الزمن ومقارنتها مع التشوهات النظرية المتوقعة . ان النتائج والتوصيات التي تم الحصول عليها في نهاية البحث يمكن أن تساهم في اختيار التصميم الأفضل للبلاطات البيتونية المسلحة ، واختيار الأبعاد المناسبة ( السماكة ) لتحسين أدائها ورفع كفاءتها لمقاومة الحمولات الخارجية المطبقة ،وكذلك بداية الطريق لمزيد من الأبحاث في هذا المجال .